PRICE COMPETITIVENESS ANALYSIS OF SEAWEED IN LEDERAGA VILLAGE, HAWU MEHARA SUBDISTRICT, SABU RAIJUA REGENCY - Hau, Desriyanti Sarilestari Djami; Bano, Maria; Darlen, Maria Fransiska; Nainiti, Selfius P.N. (Undana Press, 2025)
This research aims to analyze the price competitiveness of seaweed farming in Lederaga Village, Hawu Mehara District, Sabu Raijua Regency. The research method uses a quantitative approach with a simple random sampling technique of 30 farmers (20% of the population). Data analysis includes qualitative descriptive analysis, cost and income analysis, and SWOT analysis. The research results show that the seaweed cultivation effort using the bottom release method has an average annual income of IDR 18,602,325.63 per farmer, per year, with a production process spanning 3 seasons, indicating that this effort is classified as profitable.The strengths of the business lie in its strategic location, simple cultivation techniques, and the availability of skilled local labor. The main weaknesses include limitations in post-harvest technology and market price fluctuations. Opportunities that can be utilized include the high demand in domestic and international markets as well as the potential for creating new jobs. However, this effort also faces serious threats such as climate change, limited access to modern technology, and farmers' dependence on middlemen. The recommended strategy is to leverage strengths to seize market opportunities and increase production capacity through training and the establishment of supportive institutions.